Bringing the Reggio approach to your early years practice [ - Thornton, Linda; Brunton, Pat (Routledge, 2007)
Have you ever wondered what the Reggio approach is all about, why it works, and how it can be used to benefit the young children in your setting? This book aims to answer these questions and more. It